Employee Satisfaction and Long-Run Stock Returns, 1984–2020. Issue 3 (3rd July 2022) - Boustanifar, Hamid; Kang, Young Dae
Abstract: Economic theory predicts that (in the absence of mispricing) the excess return to socially responsible businesses is negative in equilibrium. In contrast, using the state-of-art empirical models and a sample spanning four decades (1984–2020), an equal-weighted portfolio of companies that treat their employees the best earns an excess return of 2% to 2.7% per year. The estimated alphas are positive in most periods within the sample (with no upward or downward trend) and are particularly large during crisis periods. Overall, the results suggest that the stock market (still) undervalues employee satisfaction.